EXPLORING THE EFFECTIVENESS AND STUDENTS’ PERCEPTIONS OF E-LEARNING IN ENGLISH AS SECOND LANGUAGE (ESL) SPEAKING CLASSES AMIDST COVID-19 - Iziana Hani Ismail; Nur Anneliza Abd Latip; Wardatul Akmam Din; Suyansah Swanto (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The COVID-19 outbreak quickly demonstrates the importance of adopting online education in teaching and learning. It has forced education systems worldwide to find alternatives to face-to-face interactions. Language instructors have made attempts to explore and utilise e-learning tools to enrich their teaching and assist learners in improving their language learning. This paper, therefore, attempts to shed light on the effectiveness of adopting e-learning tools in ESL speaking class and their perception of it. Fifty-three pre-university students from the Foundation Programme of the Preparatory Centre for Science and Technology were involved in this study. Data analysed in this paper were derived from a threaded online discussion via Dotstorming. The structured interview questions were carefully designed based on the objectives to elicit the studentsâ€™ opinions on the topic of interest. To explore the effectiveness of e-learning in developing the studentsâ€™ speaking skills, scores of Individual Speaking Assessment and Group Speaking Assessment of each student were collected. These assessments were marked based on the Malaysian University English Test (MUET) Speaking Rubric â€“ Task Fulfilment, Language, and Communicative Ability. The findings show that the adoption of technology in ESL speaking classes improves the studentsâ€™ speaking abilities. The thematic analysis also shows that the use of e-learning tools in language learning received positive feedbacks from the students, suggesting it would be a promising virtual platform to improve the student’s confidence, knowledge, and language.